Double Diamond Approach to Design Web-based Library Clearance Management System for Graduation Requirements - Muhammad Tosan Bingamawa; Titis Sari Putri; Kuncoro Galih Pambayun; Alauddin Maulana Hirzan; Indra Maulana Pratama (SISTEMASI, 2026)
The library clearance process is one of the main administrative requirements that students must complete before participating in the graduation process. In many higher education institutions, the library clearance process is still manual or fragmented across multiple information systems, resulting in inefficient verification, lengthy delays, and limited transparency for students and librarians. This study aims to design LibrePass, a library clearance management information system that digitizes and streamlines the submission and verification process for graduation requirements, including library clearance, submission of hard and soft copy final report documents, and other institutional requirements. This study adopts the Double Diamond approach, comprising four stages: Discover, Define, Develop, and Deliver. In the Discover stage, user needs and current business processes are identified through interviews, observations, and document analysis. Next, in the Define stage, the results of interviews and observations are synthesized to determine user experience, pain points, and user needs. Then, in the Develop stage, user flows and low- and high-fidelity wireframes are designed. The final stage is Deliver, usability testing is carried out on the prototype using the UEQ instrument with UEQ Data Analysis Tools. The test results show that all UEQ dimensions, namely attractiveness, perpicuity, efficiency, dependability, stimulation, and novelty, show excellent values, with an average score of 2,15. These results indicate that the double diamond approach is successful in designing a prototype that is acceptable and has met user needs.